Association between Exposure to Smartphones and Ocular Health in Adolescents. (3rd July 2016) - Kim, Joowon; Hwang, Yunji; Kang, Seungheon; Kim, Minhye; Kim, Tae-Shin; Kim, Jay; Seo, Jeongmin; Ahn, Hyojeong; Yoon, Sungjoon; Yun, Jun Pil; Lee, Yae Lim; Ham, Hyunsoo; et al.
ABSTRACT: Purpose : Smartphone use has dramatically increased in recent years. Smartphones may have adverse health effects, particularly on the eyes, because users stare at the screen for a much longer time than they do with ordinary mobile phones. The objective of this study was to elucidate the relationship between smartphone use and ocular symptoms among adolescents. Methods : Information on smartphone use and ocular symptoms (blurring, redness, visual disturbance, secretion, inflammation, lacrimation and dryness) related to eye fatigue and strain from 715 adolescent subjects from three cities in Korea was obtained using a structured questionnaire. Ocular health was scored using number of ocular symptoms. Odds ratios (ORs), 95% confidence intervals (95% CIs) and p -values for ocular symptoms were calculated with binomial and multinomial logistic regression models. Results : Higher prevalence rates for ocular symptoms were observed in groups with greater exposure to smartphones ( p < 0.05). Longer daily smartphone use was associated with a higher likelihood of having multiple ocular symptoms (5–7 symptoms out of 7 symptoms; p = 0.005). Excessive/intermittent use (>2 hours daily and ≤2 hours continuously) and excessive/persistent use (>2 hours daily and >2 hours continuously) compared to shorter use (<2 hours daily) were associated with multiple ocular symptoms (OR 2.18, 95% CI 1.09–4.39; OR 2.26, 95% CI 1.11–4.57, respectively). A higher lifetime exposure to smartphones was associated with a higher likelihood of having multiple ocular symptoms (OR 3.05, 95% CI 1.51–6.19; p = 0.001). Conclusion : Increasing exposure to smartphones can have a negative impact on ocular health in adolescents.